The use of deception in nursing - Teasdale, K. (Journal of medical ethics, 1995)
Arguments about the morality of the use of deception in patient care have been conducted largely in an empirical vacuum, with few data about the situations in which deception occurs. Do staff frequently deceive their patients and, if so, under what conditions? Can the consequences of deception always be foreseen? What justifications do staff use to explain their behaviour? The small-scale study reported here on the uses of deception by nurses when attempting to reassure patients provides information on these questions. The results suggest that deception can have deleterious effects on trust and increase the emotional distance between patients and staff.